With the Support of Multitudes : Using Strategic Communication to Fight Poverty through PRSPs - Odugbemi, Sina; Mozammel, Masud (London: Department for International Development, 2013)
This publication intends to improve the chances of success of Poverty Reduction Strategies (PRSs) in two ways: 1. To show policymakers how strategic communication can help them achieve some of their objectives in formulating and executing effective Poverty Reduction Strategies. 2. To give technocrats and officials, actively engaged in the execution of Poverty Reduction Strategy Papers (PRSPs), guidance on best practice, as well as lessons from a community of practice spread around the world. One of the main lessons of this study is that PRSPs are not implemented in green houses, but in very specific national contexts. Depending on the situation in each country, the following structural factors are critical to whether or not you can have genuine citizen participation in, and ownership of PRSPs: the underlying political culture can be decisive; the state of the mass media in the specific country is also a crucial factor; access to official information is the third structural impediment; the fourth is the density and capacity of civil society organizations (CSOs) in each country; and, finally, there is the vexed question of communication capacity within government. The skilled management of public opinion is an essential skill for all governments, yet the information ministry in many countries is a backwater of low skill, low pay, and low morale. This affects the implementation of Poverty Reduction Strategies in quite significant ways. This publication offers policymakers and their technical staff four important forms of support: 1. Case studies from a variety of countries on the use of communication to enhance the effectiveness of Poverty Reduction Strategies; 2. Best practice guidance on which methods are known to have been effective and which have been less so; 3. An analysis of the structural impediments to participation and country ownership; and, 4. A detailed list of further sources of information and guidance.